Modulation of chondrogenic differentiation of human mesenchymal stem cells in jellyfish collagen scaffolds by cell density and culture medium. (14th July 2015) - Pustlauk, W.; Paul, B.; Brueggemeier, S.; Gelinsky, M.; Bernhardt, A.
Abstract: Studies on tissue‐engineering approaches for the regeneration of traumatized cartilage focus increasingly on multipotent human mesenchymal stem cells (hMSCs) as an alternative to autologous chondrocytes. The present study applied porous scaffolds made of collagen from the jellyfish Rhopilema esculentum for the in vitro chondrogenic differentiation of hMSCs. Culture conditions in those scaffolds differ from conditions in high‐density pellet cultures, making a re‐examination of these data necessary. We systematically investigated the influence of seeding density, basic culture media [Dulbecco's modified Eagle's medium (DMEM), α ‐minimum essential medium ( α ‐MEM)] with varying glucose content and supplementation with fetal calf serum (FCS) or bovine serum albumin (BSA) on the chondrogenic differentiation of hMSCs. Gene expression analyses of selected markers for chondrogenic differentiation and hypertrophic development were conducted. Furthermore, the production of cartilage extracellular matrix (ECM) was analysed by quantification of sulphated glycosaminoglycan and collagen type II contents. The strongest upregulation of chondrogenic markers, along with the highest ECM deposition was observed in scaffolds seeded with 2.4 × 10 6 cells/cm 3 after cultivation in high‐glucose DMEM and 0.125% BSA. Lower seeding densities compared to high‐density pellet cultures were sufficient to induce in vitro chondrogenic differentiation of hMSCs in collagen scaffolds, which reduces the amount of cells required for the seeding of scaffolds and thus the monolayer expansion period. Furthermore, examination of the impact of FCS and α ‐MEM on chondrogenic MSC differentiation is an important prerequisite for the development of an osteochondral medium for simultaneous osteogenic and chondrogenic differentiation in biphasic scaffolds for osteochondral tissue regeneration. Copyright © 2015 John Wiley & Sons, Ltd.